Effect of SmearOFF and ethylenediaminetetraacetic acid on the surface roughness and microhardness of human root canal dentin - An ex vivo study - Raj Kumar Narkedamalli; Sandya Kini; Shubha Chhaparwal; Nidambur Vasudev Ballal (Wolters Kluwer Medknow Publications, 2022)
Introduction: The removal of smear layer using chelating agents often involves decalcification of the dentin that affects its physical properties. Hence, the objective of this study was to assess the outcome of SmearOFF and 17% ethylenediaminetetraacetic (EDTA) solutions on the surface roughness and microhardness of human root canal dentin. Materials and Methods: Twenty-three extracted human mandibular single-rooted premolars were split into 46 sections and placed into an autopolymerizing acrylic resin and were grated flat using silicon carbide abrasive papers. Forty-five samples were arbitrarily categorized into three groups as per experimental solutions used: control group (n = 15), 5 ml of 0.9% saline for 1 min + 5 ml of distilled water for 1 min, EDTA group (n = 15), 5 ml of 17% EDTA for 1 min + 5 ml of distilled water for 1 min, and the SmearOFF group (n = 15), 5 ml of SmearOFF for 1 min + 5 ml of distilled water for 1 min. The samples were then assessed for surface roughness using an atomic force microscope. The same samples were then assessed for microhardness using Vickers microhardness tester. The data were statistically analyzed using one-way analysis of variance, and the mean values were juxtaposed using Tukey's honest significant difference test. Results: The lowest surface roughness value was seen in the control group, followed by 17% EDTA and SmearOFF in an increasing order. The highest decrease in microhardness was seen in the SmearOFF group samples, followed by 17% EDTA group samples and least in the control group (P < 0.001). Conclusion: SmearOFF produced more surface roughness and caused a greater reduction in microhardness of root canal dentin in contrast to 17% EDTA.